Management of Alarming Hemangiomas with Oral Prednisolone in Infants (BIRDEM Medical Journal, 2017)
Background: Treatment of hemangiomas remains a contentious and difficult issue for the physicians as well as for the surgeons. The numerous modality of treatment for hemangiomas testifies that no single mode of treatment is entirely satisfactory in their management. However, for alarming hemangiomas oral prednisolone had been used for long with encouraging resultsMethods: From a vast number of patients with hemangiomas attending the out-patient departments (OPDs) of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Shishu Hospital (DSH), Rajshahi Medical College Hospital (RMCH) and BIRDEM General Hospital between 1999 through 2014, we had selected consecutively 462 infants with alarming hemangiomas. The whole study population (462 infants with alarming hemangiomas) received oral prednisolone at a dose of 2-4 mg/kg/day, and the results were observed sequentially in serial follow-ups.Results: About 71% patients showed substantial regression of the hemangiomas with oral prednisolone therapy after a mean duration of treatment of 6 months. Few adverse effects were associated with oral prednisolone but these were mostly transient and reversible.Conclusion: The authors assert that the management of alarming hemangiomas with oral prednisolone therapy is safe and effective.Birdem Med J 2017; 7(1): 7-11